Differential metabolites in cirrhotic patients with hepatitis B and muscle mass loss - Liu, Xuechun; Han, Lei; Bi, Shenghua; Ding, Xueli; Sheng, Qi; Jiang, Yueping; Guan, Ge; Niu, Qinghui; Jing, Xue (Frontiers in Nutrition, 2023)
Background: Sarcopenia leads to complications (infections, hepatic encephalopathy, ascites) and poor overall survival in patients with cirrhosis, in which the phenotypic presentation is loss of muscle mass. This study aimed to reveal the metabolic profile and identify potential biomarkers in cirrhotic patients with hepatitis B virus and muscle mass loss. Method: Twenty decompensated cirrhotic patients with HBV and muscle mass loss were designated Group S; 20 decompensated cirrhotic patients with HBV and normal muscle mass were designated Group NS; and 20 healthy people were designated Group H. Muscle mass loss was defined as the skeletal muscle mass index less than 46.96 cm²/m² for males and less than 32.46 cm²/m² for females. Gas chromatography-mass spectrometry was used to explore the distinct metabolites and pathways in the three groups. Results: Thirty-seven metabolic products and 25 associated metabolic pathways were significantly different in the Group S patients from Group NS patients. Strong predictive value of 11 metabolites (inosine-5'-monophosphate, phosphoglycolic acid, D-fructose-6-phosphate, N-acetylglutamate, pyrophosphate, trehalose-6-phosphate, fumaric acid, citrulline, creatinine, (r)-3-hydroxybutyric acid, and 2-ketobutyric acid) were selected as potential biomarkers in Group S patients compared with Group NS patients. Two pathways may be associated with loss of muscle mass in patients with liver cirrhosis: amino acid metabolism and central carbon metabolism in cancer. Conclusion: Seventy differential metabolites were identified in patients who have liver cirrhosis and loss of muscle mass compared with patients who have cirrhosis and normal muscle mass. Certain biomarkers might distinguish between muscle mass loss and normal muscle mass in HBV-related cirrhosis patients.